2022
DOI: 10.54393/pjhs.v3i04.125
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Low Back Pain and Disability Among Computer Operators Working in The Banks of Peshawar

Abstract: Low-back disorders are linked to awkward postures and hinders both work performance and quality of life. Objective: The aim of this study was to find the prevalence of low back pain and disability among computer operator working in banks of Peshawar. Methods: A cross sectional study was conducted on 300 computer operators. The UBL, HBL and BOK Banks in Peshawar were targeted for recruitment of participants. Non probability convenience sampling technique was used for subject’s enrolment. Both male and female pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 17 publications
(1 reference statement)
0
8
0
Order By: Relevance
“…10 of the 25 articles discovered that neck pain was the most prevalent MSDs [ 4 , [6] , [7] , [8] , 22 , 25 , 26 , 31 , 38 , 41 ] and the highest and lowest prevalence of neck pain was observed in Malaysia (78 %) [ 7 ] and Hayat, Pakistan (14.8 %) [ 42 ], while the highest and lowest prevalence of shoulder pain was found in Malaysia (72 %) [ 7 ] and Hayat, Pakistan(12.1 %) [ 42 ] respectively. In the majority of studies that were reviewed, along with the neck, the lower back, upper back, and shoulder were listed as the body parts that were most affected [ 1 , 4 , [6] , [7] , [8] , 11 , [20] , [21] , [22] , [23] , 25 , 28 , 30 , 31 , 33 , 34 , 38 , 41 ] as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…10 of the 25 articles discovered that neck pain was the most prevalent MSDs [ 4 , [6] , [7] , [8] , 22 , 25 , 26 , 31 , 38 , 41 ] and the highest and lowest prevalence of neck pain was observed in Malaysia (78 %) [ 7 ] and Hayat, Pakistan (14.8 %) [ 42 ], while the highest and lowest prevalence of shoulder pain was found in Malaysia (72 %) [ 7 ] and Hayat, Pakistan(12.1 %) [ 42 ] respectively. In the majority of studies that were reviewed, along with the neck, the lower back, upper back, and shoulder were listed as the body parts that were most affected [ 1 , 4 , [6] , [7] , [8] , 11 , [20] , [21] , [22] , [23] , 25 , 28 , 30 , 31 , 33 , 34 , 38 , 41 ] as shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…According to a study report, lower back pain was one of the leading MSDs among computer user employees. Among 25 studies, 12 articles reported that lower back pain was the most prevalent MSD throughout the body [ 1 , 11 , [19] , [20] , [21] , 23 , 24 , 28 , 30 , 33 , 34 , 42 ]. Upper back pain was also one of the top-listed MSDs next to lower back and neck pain [ 1 , 4 , [6] , [7] , [8] , 11 , [20] , [21] , [22] , [23] , 25 , 28 , 30 , 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of LBP among bank personnel is signi cantly in uenced by occupational factors, such as length of employment (>10 years) and lengthy working hours. In addition, a number of elements, including as age, persistent sickness, obesity, and physical activity, should be considered in order to prevent LBP in bank personnel [23].…”
Section: R E S U L T Smentioning
confidence: 99%